Determinants of food choice among adults in an urban community: a highlight on risk perception - Abdul Rahman, Suzanah; Ali Khan Khattak, Muhammad Muzaffar; Mansor, Najibatul Rusyda (Emerald Group Publishing Limited Howard House Wagon Lane Bingley BD16 1WA United Kingdom, 2013)
Purpose – This study was conducted to explore the underlying reasons of food choice and the association with risk perception in an urban community. The paper aims to discuss these issues. Design/methodology/approach – Using a cross-sectional design, adults between 20 and 60 years old, selected by convenience sampling from three different races; Malay, Chinese and Indian, in Sungai Petani, Kedah were surveyed. A self-administered food choice questionnaire was used and data collected were analysed using SPSS Statistic 17.0. Findings – Religion, risk perception and sensory appeal were the most prominent factors affecting food choice of respondents. Age showed significant correlation with mood and sensory appeal. Monthly income was significantly correlated with convenience, weight control and familiarity. Risk perception was found to be correlated with all motives except familiarity and religion. Research limitations/implications – A larger sample with approximately equal number of respondents from the various races would provide a more substantial overview of the trend of food choice in a multicultural population. Practical implications – This study provides an insight on factors determining the food-buying power of the community which may directly impact the commercial success of food products including modifying provisions and actions of the food industry. Originality/value – This research investigated the set priorities of an urban community in deciding the type of food for consumption which may be influenced by multicultural interactions and reported risks.